Comparison of subsidies in the Visegrad Group after the EU accession - F. Střeleček; J. Lososová; R. Zdeněk (Agricultural Economics (AGRICECON), 2009)
States of the Visegrad Four have always been the area historically connected together by common roots, tradition, culture relations and similar economic development. Economies of the Visegrad Group have reached a comparable level of development. The aim of the paper is to compare the V4 states with regard to the conditions for agricultural production and to assess the impact of the Common Agricultural Policy to the economy of agricultural holdings in the V4 states according to the FADN results.